Asalib al-Bayan: The Tasybih Language Style And Its Variants: English - Nur Fitri Ani fitriani; Ayu Afni Yurmita; Agustiar (Universitas Djuanda, 2026)
The development of global communication and Arabic language learning among non-Arabs demands a deeper understanding of classical rhetorical aspects. This study aims to analyze Tasybīh in the science of Ilm al-Bayān, examining its structure, elements, and variants, as well as evaluating its relevance to contemporary communication and Arabic language pedagogy. This qualitative literature review employs narrative and thematic approaches, integrating classical and modern references published between 2020 and 2025. The findings indicate that Tasybīh functions not only as a linguistic comparison but also as an aesthetic, emotional, and persuasive rhetorical device. Variants such as Mursal, Mu’akkad, Mufashshal, Mujmal, Balīgh, and Tamtsīl play a significant role in strengthening meaning and evoking vivid mental imagery. This study contributes novelty by linking classical Tasybīh analysis with pedagogical implications for modern Arabic language education, thereby preserving the aesthetic value, depth of meaning, and linguistic identity of classical Arabic.